Temperament correlates of stigma resistance among patients with mood disorders: a cross-sectional study - Urbani, Rossella; Chatton, Anne; Jermann, Françoise; Favre, Sophie; Richard-Lepouriel, Hélène (Frontiers in Psychiatry, 2025)
BackgroundIn the realm of mental health, stigma presents a barrier to well-being and social acceptance. However, amidst societal prejudices, stigma resistance emerges as a vital concept, reflecting individuals’ capacity to challenge negative stereotypes and maintain a positive self-concept. This paper explores the dynamics of stigma resistance, its determinants, and its implications for mental health outcomes, focusing specifically on mood disorder patients.MethodsAdult patients with mood disorders who provided written informed consent were consecutively recruited. Data were collected between 2020 and 2022 at the Mood Disorder Unit of the Geneva University Hospitals. Participants were assessed using the Mini International Neuropsychiatric Interview (MINI), Montgomery–Åsberg Depression Rating Scale (MADRS), Young Mania Rating Scale (YMRS), Internalized Stigma of Mental Illness scale (ISMI), Temperament Evaluation of Memphis, Pisa, Paris and San Diego Autoquestionnaire (TEMPS-A), and the Quality of Life in Bipolar Disorder scale (QolBD). For all scales, higher scores indicate greater symptom severity or higher levels of the measured construct.ResultsIn this sample, the majority of patients were women, approximately one-third were single, and about half had completed high school or university education. Most participants were well integrated in the labor market. Multiple linear regression analyses indicated that shorter illness duration, higher hyperthymic temperament scores, and better quality of life were significantly associated with greater stigma resistance. Additionally, a positive trend was observed between internalized stigma and stigma resistance, although this did not reach statistical significance.ConclusionsOur study highlights the complex interplay of factors influencing stigma resistance among individuals with mood disorders. Understanding these dynamics is crucial for developing targeted interventions to enhance resilience and improve outcomes in this population.